Copper modified waste fly ash as a promising catalyst for glycerol hydrogenolysis - Rode, C. V.; Mane, R. B.; Potdar, A. S.; Patil, P. B.; Niphadkar, P. S.; Joshi, P. N. (Catalysis Today, 2012)
Several catalyst formulations using waste fly ash along with Cu were prepared and characterised by XRD, BET and TEM. These catalysts were also evaluated for the first time for hydrogenolysis of glycerol to 1,2 propanediol (1,2-PDO) in a batch reactor under 52 bar H-2 pressure in the temperature range of 473-513 K conditions. The fly ash pretreated by alkali using the fusion method and impregnated with Cu showed higher activity and stability for glycerol hydrogenolysis. Due to pretreatment with alkali at high temperature, transformation of alpha-quartz to the tridymite phase of SiO2 occurred. More importantly, use of alkali either during the pretreatment or the Cu loading step resulted in a high dispersion on the surface which was responsible for higher glycerol conversion and 1,2-PDO selectivity. The effects of temperature, Cu loading and solvent on glycerol conversion and product selectivities were also studied in this work. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: 1; 2-Propanediol; Alkali fusion; Cu loading; Fly ash; Glycerol hydrogenolysis

Synthesis of advanced asbestos-free material using rice husk ash and marble waste for thermal insulation applications - Verma, Sarika; Bajpai, Harsh; Suresh, S.; Mili, Medha; Gupta, Ritesh Kumar; Shetty, Rohit; Kamble, Sanjay; Khan, Mohd. Akram; Hashmi, S. A. R.; Srivastava, A. K. (Biomass Conversion and Biorefinery, 2023)
The importance and utilization of advanced thermal insulating materials increase due to their broad and irreplaceable energy conservation role. This paper describes the novel way of achieving insulating material. In two waste by-products, namely rice husk ash (RHA), agriculture waste, and marble waste powder (MWP), industrial waste has been utilized to make asbestos-free advanced material for thermal insulation. A novel method for making asbestos-free advanced material for thermal insulation using RHA and marble waste's inherent characteristics has developed mechano-chemical for appropriate physico-chemical consolidation, densification, and ceramic processing route. The Si and Ca sources undergo a series of chemical transformations accompanied by mass transfer and thermal reactions during the synthesis process. The formation of this silicate compound occurs due to the presence of higher contents of CaO in marble waste powder (MWP) and silica in rice husk ash (RHA), resulting in thermal insulating characteristics in the advanced thermal insulation material (ATIM). Raman spectra of ATIM after heating at 1100 degrees C were mainly amorphous, which had a broad peak at 1072 cm(-1). This shows thermal transformation occurs after the heating process, the admixture of tailored powder, and fly ash (FA). The density of the ATIM is found to be 1150 kg/m(3). The phase transformation (glass transition temperature) was found in all the samples between 600 and 800 degrees C. The mechanical properties, namely the compressive strength and impact strength evaluation test, showed that the material meets the standard specifications for ceramic tiles. The thermal conductivity (W/mK) was calculated from different temperature 30, 50, 100,150, and 200 degrees C and found to be 0.571, 0.541, 0.516, 0.498, and 0.477, respectively. According to the test results, it is concluded that ATIM from MWP, RHA, and FA were excellent insulating components. The novel feature of the reported process is the development of non-toxic and asbestos-free thermal insulating low-cost material wherein chemically designed and mineralogically formulating desired phases lead to the homogeneous and effective thermal insulating matrix. The process is feasible, simple, cheap, and highly energy-efficient, increases production efficiency, and is environmentally friendly. The widespread use of advanced material for a broad application spectrum ranges from aerospace, automobile, electronics, transportation, construction, to other industries.
Keywords: Asbestos; Fly ash; Marble waste; Material; Rice husk ash; Thermal insulation

Fly-ash-based geopolymers: leachability and solid-state NMR investigations - Nadol, Athulya; Ajithkumar, T. G.; Singla, Rashmi; Alex, T. C.; Kumar, Sanjay; Bhatt, Himal; Deo, M. N.; Sen, Debasis; Ambashta, R. D.; Bajpai, R. K.; Shivakumar, Y. C.; Manohar, S. (Bulletin of Materials Science, 2026)
This study aims to explore how leaching impacts the microstructure of a selected fly ash-derived geopolymer and evaluate its potential for near-surface disposal of radioactive waste. The uniqueness of this geopolymer formulation is its ability to form an aluminosilicate network that remains resistant to structural changes upon contact with water. The leach index of base elements such as Ca, Al, Na and Si was between 11 and 13, suggesting that the formulation is superior to Portland cement or conventional hydraulic cement. Solid-state NMR reveals that the water-interacted specimen has no contamination of the zeolite phase and all the Na is incorporated into the aluminosilicate geopolymer gel network, which also confirms that the glassy network of the geopolymer is responsible for imparting low leachability of base elements from its structure, and there is no labile sodium available for exchange as in zeolites.
Keywords: aluminosilicate network; Fly ash; Geopolymers; leaching; Solid-state NMR